PENGETAHUAN IBU HAMIL TENTANG OBESITAS DI RSUD. TENGKU MANSYUR KOTA TANJUNG BALAI - Tanjung, Meni Fuzi Astuti (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
In 2004-2005 the Indonesian Health Demographers Survey found about 20% of the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) caused by obesity caused by pre-eclampsia symptoms. A descriptive study has been conducted to determine the level of knowledge of pregnant women about obesity by Tengku Mansyur Hospital Tanjung Balai City in 2021 based on education, parity. This population is all pregnant women who have their pregnancy checked by Tengku Mansyur Hospital Tanjung Balai City in 2021 as many as 33 people and the entire population is based on samples. From the results of research on the level of knowledge of pregnant women about obesity by Tengku Mansyur Hospital, Tanjung Balai City in 2021, the majority of respondents have sufficient knowledge (57.58%) and the minority has less knowledge as much as 14%. Based on the majority age 20-35 years as many as 19 people (57.58%) with sufficient knowledge and broadly aged <20 years 2 people (6.06%) are less knowledgeable. Based on education with high school education as many as 7 people (21.21%) have sufficient knowledge and a minority with elementary education as many as 3 people (9.10%) have sufficient knowledge. And based on parity, the majority had less knowledge in the primigravida group as many as 9 people (27.27%) and the minority with sufficient knowledge in the primigravida group as many as 1 person (3.03%). It is hoped that the role of health workers, especially midwives, is to provide health education and counseling about obesity in pregnant women.